Family transition in South Asia: Provision of social services and social protection - W. Indralal De Silva (Asia-Pacific Population Journal, 2005)
Family may be defined as a group of persons related to a specific degree, through blood, adoption or marriage. The difficulty is that comparative data on the family in the broad definition of the term are not available. The available statistics relate to households, defined by location, community or living arrangements. Surveys and censuses usually cover all households, not merely family households. Nevertheless, the latter type constitutes a major proportion enabling the characteristics of the totals to be identified as those of family households. For many demographic, socio-economic and political reasons, family members may disperse and consequently, the size of the household could be reduced although the size of the family would remain unchanged. In Asian countries, most young people live with their parents after marriage and later move to another place whenever custom imposes or the economic condition of the new couple permits. Lloyd and Duffy (1995) believe that, beyond this natural ebb and flow of family members, families are becoming more dispersed. Young and elderly adults, spouses and other relatives who might otherwise have shared a home are now more likely to live apart from one another. In 2004, the United Nations observed the tenth anniversary of the International Year of the Family. Thus, it appears timely to review some of the trends, such as fertility, marriage dissolution, migration, urbanization and ageing, that affect the family in the region.